RESULTS OF TESTING THE IMPROVED SEPARATOR-PURIFIER IN A COTTON GINNING PLANT (Conferencea, 2023)
The report talks about the results of the tests conducted in the production conditions of the cotton ginning enterprise of the pilot copy of the improved planar drum separator-cleaner developed at the "Pakhtasanoat Scientific Center" JSC.